Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/cddis.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Calcium flux-independent NMDA receptor activity is required for Aβ oligomer-induced synaptic loss

Abstract: Synaptic loss is one of the major features of Alzheimer's disease (AD) and correlates with the degree of dementia. N-methyl-d-aspartate receptors (NMDARs) have been shown to mediate downstream effects of the β-amyloid peptide (Aβ) in AD models. NMDARs can trigger intracellular cascades via Ca2+ entry, however, also Ca2+-independent (metabotropic) functions of NMDARs have been described. We aimed to determine whether ionotropic or metabotropic NMDAR signaling is required for the induction of synaptic loss by Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 44 publications
3
68
0
Order By: Relevance
“…Another plasticity-relevant pathway that has been implicated in metabotropic NMDAR actions is the activation of p38 MAPK (Nabavi et al, 2013; Birnbaum et al, 2015) which has been shown to be central to DP (Liang et al, 2008) and AMPAR endocytosis (Huang et al, 2004) However, the two pathways mentioned above are just two options how mGluR1 and metabotropic NMDAR actions could control the expression of DP. Future studies are required to identify the precise signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another plasticity-relevant pathway that has been implicated in metabotropic NMDAR actions is the activation of p38 MAPK (Nabavi et al, 2013; Birnbaum et al, 2015) which has been shown to be central to DP (Liang et al, 2008) and AMPAR endocytosis (Huang et al, 2004) However, the two pathways mentioned above are just two options how mGluR1 and metabotropic NMDAR actions could control the expression of DP. Future studies are required to identify the precise signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A change in intracellular calcium levels is involved in the pathogenesis of AD [4546]. In particular, increased intracellular calcium is related to cognitive impairment through neuronal degeneration such as Aβ accumulation and synaptic loss [47]. Aβ decreases dendritic spine density, suppresses long-term potentiation (LTP), facilitates long-term depression (LTD), and impairs learning and memory [48].…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether tau toxicity in APP transgenic cultures was mediated by ion flux through NMDA receptors, we first treated cultures with clinically relevant concentrations (1 µM and 10 µM, according to (Xia 2010 [10] )) of the NMDAR open channel blocker memantine. 1µM Memantine has been shown to block synaptic transmission in organotypic slices (Birnbaum 2015 [9] ). At both concentrations, memantine treatment completely abolished tau-dependent cell death in APP transgenic cultures (Fig.…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
“…independent of ion flux, has also been described (Nabavi 2013 [7] ) (Tamburri 2013 [8] ). It has been recently shown that oligomeric Aβ caused synaptic loss in hippocampal slice cultures via NMDAR signaling but independently of calcium influx (Birnbaum 2015 [9] ). In the present study we investigated, whether the tau-dependent neuronal cell death in APP transgenic cultures depends on ionotropic (calcium influx) or metabotropic NMDAR functions.…”
Section: Introductionmentioning
confidence: 99%